Lignin-based acrylate adhesive without organic solvent processing. (1st February 2023) - Yan, Yongping; Li, Yao; Han, Ying; Ma, Zihao; Sun, Yanning; Li, Jigeng; Sun, Guangwei
Abstract : The introduction of lauryl methacrylate enhances the compatibility of lignin, which in turn enhances the infiltration and mechanical strength of the adhesive, and can replace the use of organic solvents. Abstract : As a green adhesive, lignin-based acrylate adhesives have a promising future in substitute commercial adhesives owing to their cost-effectiveness, and environmental friendliness. In this work, a green and convenient strategy for the fabrication of lignin-based acrylate adhesives was developed via the introduction of lauryl methacrylate with a low glass transition temperature (−62 °C) into the chemical structure of lignin to improve the compatibility, toughness, strength and wettability of lignin-based adhesives. With the introduction of lauryl methacrylate, the shear strength of the lignin-based adhesive reached 5.10 MPa, which is 114% higher than the traditional acrylate adhesive. Moreover, the lignin-based adhesive also exhibits excellent hydrophobicity and high shear strength after 12 h of immersion in water. This work not only provides a new strategy for the fabrication of economical, green, and sustainable lignin-based acrylate adhesives without the participation of organic solvents, but also achieves the value-added utilization of lignin.